MEMAHAMI PRODUK PEMBIAYAAN LEMBAGA KEUANGAN SYARIAH BERBASIS JUAL BELI ISTISHNA’ - Moh Rifky Mubarok; Moh. Karim (Jurnal Ekonomi Syariah Darussalam, 2026)
With the rapid advancements in technology facilitating transactions, people have gained numerous conveniences in their shopping experiences. One prominent example is online retail, commonly referred to as e-commerce. As a result, the community frequently utilizes platforms like Shopee, Tokopedia, Lazada, Bibli, and Bukalapak for buying and selling activities. Online commerce entails a transaction process where the buyer places an order and makes a payment either beforehand, during, or afterward within a specified timeframe, all made possible by technological advancements. Additionally, specific contracts, such as istisna contracts, are utilized in carrying out these transactions. The aim of this research is to explore in greater detail the use of istisna contracts in online purchasing. This paper employs a qualitative method with a descriptive approach. The analysis method used is content analysis, concentrating more deeply on the acquired information. The findings reveal that Islamic transactions involving istisna contracts, the basis of Shari'ah, parallel istisna, and how these transactions are structured. Keywords: Istishna, Islamic Financing, Financial Institutions